Comparison of Hematological Profile Changes in Pre- and Post-Chemotherapy Treatment of Cancer Patients - Muhammad Ilyas Khan, Yasmeen Bibi, Bilal Ahmed, Abdul Haseeb, Yousaf Khan, Kaleem Ullah, Sajjad Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cancer being the principle cause of death in both developed and developing countries; the problem is more likely to increase around the globe due to rapid population growth and aging. The aim of this study was to find the effect of chemotherapy on hemoglobin, total leucocytes count, and platelets level. Materials and Methods: A cross-sectional study was conducted and through conveinent sampling technique, blood samples from cancer patients were studied in a pathology lab at the INOR cancer hospital in Abbottabad, KPK, Pakistan. During the months of September to December 2017, 200 cancer patients visited INOR Cancer Hospital Abbottabad. The haematology analyzer Mindray BC 5000 was used to analyse various parameters of cancer blood samples. The effects of chemotherapy on blood counts were documented in Microsoft Excel 2007. Results: A total of two hundreds cancer patients were recruited in the study. Among total, 44% (n=88) were male patients and 46% (n=112) were female patients. all hematological parameters including hemoglobin, total leucocytes count, and platelets level were decrease after chemotherapy. Conclusion: Chemotherapy is the most effective method of treating cancer patients. It progressively restores normal levels of WBCs, RBCs, Hb, and PLTs. It is beneficial in order to reduce the blood cells burden on patients. Moreover, it is determined that blood cells become normal after chemotherapy. Keywords: Hematological parameters, Blood cancer, Chemotherapy, Bone maroow, Tumor, Cancer patients